2017
DOI: 10.1007/s10792-017-0547-x
|View full text |Cite
|
Sign up to set email alerts
|

The overlapping spectrum of flat irregular pigment epithelial detachment investigated by optical coherence tomography angiography

Abstract: Central serous chorioretinopathy, type 1 CNV, and the pachychoroid spectrum of diseases cause abnormalities in the choroidal circulation that make the overlying RPE dysfunctional, resulting in flat irregular PED. Discrimination between avascular and vascular flat irregular PEDs is crucial for a good visual outcome, but since chronic alterations of the RPE can compromise the diagnostic specificity of FA and ICGA, OCT angiography may become a fundamental tool to differentiate these clinical entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…This sign has been previously described as a pathological feature in polypoidal choroidal vasculopathy and PEDs in pachychoroid diseases [14], representing the neovascular proliferation and exudation from the polyps [20]. Chug et al discussed the convergent mechanism of formation between CSC and polyps due to hyalinization of choroidal vessels, along with replacement of the smooth muscle component by amorphous pseudocollagenous tissue [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This sign has been previously described as a pathological feature in polypoidal choroidal vasculopathy and PEDs in pachychoroid diseases [14], representing the neovascular proliferation and exudation from the polyps [20]. Chug et al discussed the convergent mechanism of formation between CSC and polyps due to hyalinization of choroidal vessels, along with replacement of the smooth muscle component by amorphous pseudocollagenous tissue [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 96%
“…80% of eyes a hyperfluorescent plaque with surrounding areas of hypofluorescence was observed in the late phase of ICGA angiography; 20% of eyes exhibited an ICG hypofluorescent washout. However, the persistence or vanishing of choroidal staining is difficult to evaluate in the late stage angiograms in presence of RPE atrophy, as previously described [ 16 ]. No signs of leakage or choroidal polyps were evident on the mid or late stage angiograms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study results are generally in agreement with reports from previous studies that associated small, flat-irregular PEDs with chronic CSCR. 15,2024 The overall prevalence of PED in CSCR has been reported between 53% and 100%; 22,25,26 however, most studies have not differentiated between PED types. Ersoz et al 22 reported, in one of the largest retrospective cohort studies in 811 patients, a PED prevalence of 83% concluding that its presence is frequently associated with a chronic rather than acute course and it was only recently that studies have demonstrated possible influence of the PED shape on the course of the disease.…”
Section: Discussionmentioning
confidence: 99%